2017
DOI: 10.1177/1369433217739708
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis on seismic behaviors of T-shaped concrete-filled steel tubular columns with reinforcement stiffeners

Abstract: A numerical analysis based on previous experiment has been carried out on T-shaped concrete-filled steel tubular columns subjected to constant axial compressive load and cyclic lateral loads. Tensile bar stiffeners were introduced to be welded on inside surfaces of steel tube to postpone its local buckling and to enhance the confinement of steel tube for concrete. A modified fiber-based method was developed to establish numerical modeling program of specimens' cyclic behavior, incorporating the effect of stiff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Surface-to-surface contact was usually used for the interaction simulation of the steel tube and concrete, which includes normal contact and tangential slip and a surface-based interaction with hard contact in the normal direction. e Small sliding and the Coulomb friction coefficient of 0.4 in the tangential direction to the interface is used to simulate the interfacial behavior between steel tube and core concrete [20], in which the sliding formulation is finite sliding. Tie constraint can couple two separate surfaces so that no relative motion occurs between them.…”
Section: Materials Constitutive Relationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surface-to-surface contact was usually used for the interaction simulation of the steel tube and concrete, which includes normal contact and tangential slip and a surface-based interaction with hard contact in the normal direction. e Small sliding and the Coulomb friction coefficient of 0.4 in the tangential direction to the interface is used to simulate the interfacial behavior between steel tube and core concrete [20], in which the sliding formulation is finite sliding. Tie constraint can couple two separate surfaces so that no relative motion occurs between them.…”
Section: Materials Constitutive Relationsmentioning
confidence: 99%
“…Tao et al [10] proposed the stiffened concrete-filled thin-walled hollow steel structural (HSS) stub column, which can alleviate local buckling and improve the bearing capacity of square and rectangular concrete-filled steel tubular columns, but it has no obvious effect on ductility. Cai et al [11][12][13][14][15][16][17][18][19][20] investigated the steel tube with binding bars, and horizontal restraint rods were installed along the steel tube wall. e research showed that the restraint effect of the steel pipe on the core concrete and the bearing capacity and ductility of the CFST columns have been improved.…”
Section: Introductionmentioning
confidence: 99%
“…Concrete-filled steel tubular (CFST) columns have been widely applied in practical engineering owing to the excellent structural performance. The specialshaped column structure of CFST inherits the advantages of high bearing capacity and good ductility of CFST structure (Liu et al, 2018a). Meanwhile, the steel tube can be used as the formwork for concrete pouring and simplified the construction process.…”
Section: Introductionmentioning
confidence: 99%
“…Since the flange of the T-shaped stiffener is partly enclosed in the concrete, the joint working performance of the stiffener and the concrete can be fully utilized, and the local buckling performance of the steel tube wall can be greatly improved. In order to delay the local buckling of steel tubes and improve the restraint performance of steel tubes on concrete, Liu [23] welded tensile reinforcing bars on the inner surface of steel tubes. A modified fiber-based numerical modeling method was developed to study the specimens' cyclic behavior, incorporating the effect of stiffeners on postponing the steel tube's local buckling and the confinement for concrete.…”
Section: Introductionmentioning
confidence: 99%